Lipase-catalyzed synthesis and characterization of a novel linear polyamidoamine oligomer - Monsalve, Leandro Nicolas; Kaniz Fatema, M.; Nonami, Hiroshi; Erra Balsells, Rosa; Baldessari, Alicia (Polymer)
A linear polyamidoamine oligomer was obtained by polymerization of ethyl acrylate and N-methyl-1,3-diaminopropane, catalyzed by the Candida antarctica lipase. Depending on the reaction conditions such as substrates concentration, solvent and enzyme:substrate ratio, the enzyme catalyzes the polymerization reaction or Michael adducts formation. The polymeric material, characterized by FTIR, 1H and 13C NMR and UV-MALDI-TOF-MS, shows low molecular weight and high monodispersity. The activity showed by C. antarctica lipase in the polymerization reaction is highly selective and allows to obtain a product with potential biomedical applications in mild condition reactions and low environmental impact. Fil: Monsalve, Leandro Nicolas. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Kaniz Fatema, M. Ehime University; Japón Fil: Nonami, Hiroshi. Ehime University; Japón Fil: Erra Balsells, Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones en Hidratos de Carbono. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones en Hidratos de Carbono; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina